Interactions between Pax6, Barhl2 and Shh in the early patterning of the mammalian diencephalon - Parish, Elisa Victoria (The University of Edinburgh, 2016)
Diencephalic development requires the transcription factors Pax6 and Barhl2 in order to proceed correctly. Both genes are necessary for the normal development of the organizer region known as the zona limitans intrathalamica (ZLI). The ZLI goes on to pattern the diencephalon via its secretion of the morphogen Shh, which inhibits the expression of Pax6. These findings suggest that interactions between Pax6, Barhl2 and Shh may be involved in the control of diencephalic development. This project aims to characterise these interactions and investigate their roles. The expression domains of Pax6 and Barhl2 were mapped during the early development of the mouse diencephalon. Qualitative approaches were employed to confirm the high complementarity of their expression domains and obtain evidence of a mutually repressive relationship existing between the two genes. The findings from a quantitative analysis suggested that this inhibition is incomplete within the thalamus. Investigations using the Pax6-null mutant mouse confirmed that in the absence of Pax6 the thalamic Barhl2 expression domain expands beyond the ventricular zone, the site of thalamic neurogenesis. The influence of Shh signalling on the expression of Pax6 and Barhl2 was investigated via a gain-of-function approach utilising in utero electroporation to activate the Shh pathway. This led to a downregulation of both Pax6 and Barhl2 within the thalamus. In Shh loss-of-function experiments drug treatment with the Shh antagonist vismodegib led to an upregulation of Barhl2 and the loss of the GABAergic pTh-R in the Pax6-null mutant thalamus, but not in the wild type thalamus, suggesting that Pax6 and Shh may be required to inhibit Barhl2 in order for GABAergic neurogenesis to proceed. Barhl2 expression was detected in the Shh-null mutant mouse confirming that, in contrast with their homologues in Drosophila, Shh may be expressed downstream of Barhl2. Together these findings have been used to develop a novel model of thalamic development in which Barhl2 induces ZLI development, inhibition of Barhl2 by Pax6 restricts its expansion, and secretion of Shh by the ZLI then goes on to inhibit Pax6 and Barhl2 in the pTh-R while mutual repression between Pax6 and Barhl2 modulates neurogenesis in the more caudal regions of the thalamic neuroepithelium.
Keywords: Pax6; Barhl2; Shh; diencephalon; patterning; electroporation; ZLI